The Portrayal and Branding of British Columbia Offshore Schools on Provincial Government Websites - Alexander, Ian; Werbitsky, Laura (Comparative and International Education / Éducation comparée et internationale, 2024)
This article examines how British Columbia (BC) portrays its offshore school program on its government websites. BC offshore schools currently operate in 11 countries, teaching the provincial curriculum to students from the local host country. Our critical discourse analysis of BC provincial government websites and videos shows that the curriculum is portrayed as a brand and the program’s rationales and goals are inconsistent. BC portrays its curriculum as a global brand that is more progressive, modern, and worldly than the countries that host offshore schools. However recent BC curriculum initiatives, such as Indigenous perspectives and knowledge, core competencies, and place-based learning are mostly absent from the discourses on the websites and videos. Based on these findings, we propose that BC revisit the rationalization for the offshore school program and how it is officially portrayed because the portrayal of curriculum as a branded product blurs the lines between public and private spaces.